Sliding wear of SiC reinforced duplex stainless steel via TIG torch sur-face melting technique - Maleque, Md. Abdul; Azwan, M. K.; Muhammad M., Muhammad M. (Bentham Science Publishers, 2020)
Background: Duplex stainless steel (DSS) has gained increasing interest in recent years for a number of applications as structural materials in various industrial sectors of the petrochemical process plant, marine engineering and automotive industries. However, this material has experienced hardness and wear failure in the service. Therefore, new development in the surface modification for DSS is required to explore the possibility of producing a hard modified surface layer of SiC resolidi-fied layer by TIG torch surface melting technique.